Integrating Hybrid Team-Based and Case-Based Learning in Dental Education Transformation - Sidra Abid; Humna Rafiq (Pakistan Journal of Medical Research)
In the context of dental education, the adoption of Hybrid team based learning (TBL) and case based learning (CBL) is a promising approach towards meeting the needs of whether competencies-based or outcome-based medical education by promoting active, collaborative, and self-directed learning. This hybrid methodology retains the advantages of both paradigms, as demonstrated in the existing literature. In this vein the combination of CBL and TBL at tertiary level contributes to the improvement of students` academic performance and engagement so the hybrid form of CBL and TBL is qualified to narrow the gap between secondary and higher educational systems creating active learning and positive social interdependence1 and this means that this tactic allows students not only to participate in the topic fully, but also to encourage ethical-based decision- making.2  Hybrid TBL is the method where students learn all concepts of their studies in a way that students are really being engaged. Never do Hybrid TBL processes focus on passive learning, as both team spirit and individualism are encouraged. Instead, it is a more interactive process in that students are required to contribute in discussions, exchange ideas based on case study readings, or even collaborate in project teams. The research findings indicate that a variety of strategies for TBL are beneficial not just in terms of enhancing students' perception of learning outcomes, but also shows improvement in competencies and efficacy in dental education.3 It is a matter of involving dynamic participation, collaboration, and the development of critical abilities. The CBL is another way to fill the TBL ‘gap’ which is a student-centered learning method in which regular clinical scenarios are solved as case reports, responsibilities of Student-to-Student teaching in particular topics to promote professional diagnosing, and ethical practice planning. The CBL helps students step closer to actual dental practice by allowing them to immerse themselves in genuine cases. The idea is that students are more likely to apply theoretical knowledge to read scenarios that emulate the issues they will face in their actual dental practice. Learning CBL allows students to improve clinical reasoning, think critically, and cooperate more fully.2